Human Capital Investment in Universities: A Case Study of Gedo International University - Abdiaziz , Abdullahi Hussein (International Journal of Developing Country Studies, 2024)
Purpose: This study investigates the role of Gedo International University (GIU) in advancing human capital investment within the Beledhawa District, Somalia. It explores the impact of higher education on socio-economic development, focusing on GIU’s contributions to healthcare, education, and regional growth. Methodology: The research employs a qualitative case study approach, including semi-structured interviews with graduates, faculty, and students, alongside document analysis of institutional reports and district-level socio-economic data. Findings: GIU has significantly contributed to local development by producing skilled professionals in healthcare and education. Its graduates are instrumental in improving service delivery and fostering economic opportunities, despite challenges such as limited resources and the absence of key academic programs. GIU has also catalyzed the establishment of secondary schools in the district, promoting broader access to education. Unique Contribution to Theory, Practice, and Policy (Recommendations): This study highlights the critical role of higher education in human capital development in underserved regions. It recommends strategic partnerships with NGOs and private sectors, expanded academic offerings in agriculture and veterinary sciences, and the establishment of satellite campuses. These measures can enhance GIU’s capacity to address the region’s socio-economic needs and serve as a model for universities in similar contexts.